+0  
 
0
145
1
avatar
write the nth term for 2,-4,6,-8
Guest Mar 22, 2012
Sort: 

1+0 Answers

 #1
avatar+3071 
0
f(n)=2*n*(-1)^(n+1)

f( 1 ) = 2*n*(-1)^(1+1) = 2*1*(-1)^2 = 2
f( 2 ) = 2*n*(-1)^(2+1) = 2*2*(-1)^3 = -4
f( 3 ) = 2*n*(-1)^(3+1) = 2*3*(-1)^4 = 6
f( 4 ) = 2*n*(-1)^(4+1) = 2*4*(-1)^5 = -8
admin  Mar 22, 2012

19 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details